Resveratrol-Elicited PKC Inhibition Counteracts NOX-Mediated Endothelial to Mesenchymal Transition in Human Retinal Endothelial Cells Exposed to High Glucose - Roberta Giordo; Gheyath K. Nasrallah; Anna Maria Posadino; Francesco Galimi; Giampiero Capobianco; Ali Hussein Eid; Gianfranco Pintus (MDPI AG, 2021)
Diabetes-associated long-term hyperglycaemia leads to oxidative stress-mediated fibrosis in different tissues and organs. Endothelial-to-mesenchymal-transition (EndMT) appears to play a role in diabetes-associated fibrotic conditions. Here, we investigate whether EndMT is implicated in the diabetic retinopathy fibrotic process and evaluate the possibility that resveratrol could counteract EndMT by inhibiting high glucose (HG)-induced increases in ROS. Primary Human Retinal Endothelial Cells (HRECs) were either pre-treated for 24 h with 1 µM resveratrol or left untreated, then glucose (30 mM) was applied at 3-day intervals for 10 days. qRT-PCR and ELISA were used to detect mRNA or protein expression of endothelial markers (CD31, CDH5, vWF) or mesenchymal markers (VIM, αSMA and collagen I), respectively. Intracellular ROS levels were measured with carboxy-DCFDA, while NOX-associated ROS levels were evaluated using the NADPH-specific redox biosensor p47-roGFP. Treatment of HRECs with HG increased intracellular ROS levels and promoted phenotype shifting towards EndMT, evidenced by decreased expression of endothelial markers concomitant with increased expression of mesenchymal ones. HG-induced EndMT appears to be mediated by NADPH-associated ROS generation as pre-treatment of HRECs with resveratrol or the NADPH inhibitor, diphenyleneiodonium chloride (DPI), attenuated ROS production and EndMT transition, suggesting that the effect of resveratrol on HG-induced ROS occurs via down-regulation of NADPH oxidase. It is worth noting that resveratrol or Chelerythrine, a Protein kinase C (PKC) inhibitor, reduce ROS and EndMT in HG-exposed cells, suggesting that NADPH activation occurs via a PKC-dependent mechanism. Taken together, our results provide the basis for a resveratrol-based potential protective therapy to prevent diabetic-associated complications.